PATTERNS AND CONSEQUENCES OF VETO POWER IN GENOCIDE RESPONSE: A COMPARATIVE STUDY ON SYRIA AND PALESTINE - Rana, Ariq Taqi (Student Journal of International Law, 2025)
The United Nations Security Council (UNSC) faces significant challenges in addressing genocide due to the veto power granted to its permanent members under Article 27(3) of the UN Charter. This research analyzes the impact of veto power on the UNSCs accountability and effectiveness, focusing on the conflicts in Syria and Palestine. Through normative legal research and a comparative approach, the study characterizes the crimes committed by the Assad regime and the Israeli government as genocide using Genocide Watchs Ten Stages framework. It then examines how Russia and the United States have prioritized geopolitical interests over humanitarian concerns, enabling impunity and obstructing international legal accountability. Distinct from previous works, this study advances a legal critique grounded in jus cogens norms and the UN Charters purposes and principles. It proposes reforms such as a supermajority override and amendment of Article 27 to empower non-permanent members and strengthen the UNSCs capacity to respond effectively to genocide.